The Concept of Islamic Religious Education in the Story of Hayy ibn Yaqzan by Ibnu Thufail and Its Relevance to Informal Education - M. Mahdi Al Fattah; Zulkipli Nasution (Universitas Muhammadiyah Enrekang, 2025)
This study aims to examine the concept of Islamic religious education in the story of Hayy ibn Yaqzan Ibn Yaqzan by Ibn Tufail and its relevance to the practice of informal education. The method used is qualitative research with a literature study approach. Data were obtained from the primary text and supporting literature, analyzed descriptively. The results show that Hayy ibn Yaqzan acquired knowledge through observation, experimentation, reasoning, intuition, and habituation—all of which reflect the principles of informal education based on fitrah (natural disposition), experience, and spirituality. This story is relevant as an inspiration for developing a contextual, independent, and life-integrated approach to Islamic religious education.